PWE-175 Simple Intervention Improves Outcome in Delivery of Parenteral Nutrtion. (4th June 2013) - Davies, P; Bowness, J; Whittingham, C; Bassi, A
Abstract : Introduction: Recent report by NCEPOD into hospital care of patients receiving parenteral nutrition (PN) suggested that only 19% adult patients had PN care that was considered to represent good practise. An initial audit (retrospective audit over six months) in our hospital suggested lack of quality control at the point of initiation of PN. Simple remedial actionwas introduced and the audit cycle was completed to assess the impact of mandatory minimal set documentation prior to initiation of PN. Methods: A mandatory request sticker was introduced which prompted the clinical team to document why enteral nutrition is inappropriate and duration of inadequate enteral intake, the clinical purpose and goal of PN and expected duration of PN. A prospective re-audit was performed to assess any change over the same six month period. Results: The initial audit included 43 patients and 34 patients received PN during the reaudit period. Administration of PN was predominantly in surgical (47%) or critical care (20%) areas. The indication was documented in the case notes in 88% of cases (initially 43%), and considered appropriate by the nutrition team in 94% of cases (initially 67%). There were unreasonable delays in 21% of cases (initially 29%), mostly related to delays in placing appropriate central venous access. The treatment goal was documented in 82% of cases (initially 36%). Alternatives were considered in 100% of cases (initially 64%) and an appropriate assessment was made in 97% of cases (initially 69%). TPN was reviewed and monitored appropriately in the initial audit and there was no change in the re-audit. Metabolic complications occurred in 38% of cases (initially 52%), all cases were managed appropriately. Nine percent of patients received PN for fewer than 5 days (initially 12%) but the vast majority received an appropriate course length. Seventy four percent of patients were weaned onto oral diet (initially 67%) and 6% of patients died during their stay (initially 17%). Conclusion: A relatively simple intervention, involving no additional cost, vastly improved the delivery of PN in our hospital. Mandatory information prior to starting helped to focus the thoughts of the requesting clinicians to decide on the appropriateness of using PN. This simple win-win strategy can be easily adopted in other hospitals to improve delivery of PN. Disclosure of Interest: None Declared.